A new thermal-stable truxene-based hole-transporting material for perovskite solar cells. (February 2016) - Wang, Jiang; Chen, Yu; Liang, Mao; Ge, Gaoyang; Zhou, Renjie; Sun, Zhe; Xue, Song
Abstract: Developing effective hole-transporting material is critical to achieve high efficiency CH3 NH3 PbI3 perovskite solar cells. A new thermal-stable truxene-based material, 2, 7, 12-tri(N, N-di(4-methoxyphenyl)amino)-5, 5′, 10, 10′, 15, 15′-hexapropyltr-uxene, has been synthesized by a facile route. A reference compound, 1, 3, 5-tris(di-p-anisylamino)benzene, was prepared as well. Their optical, electronic properties, thermal stability and photovoltaic performances were investigated. This new truxene-based material exhibits a high decomposition temperature (432 °C), a high glass transition temperature (134 °C), and a suitable highest occupied molecular orbital level well-matched with the valence band of CH3 NH3 PbI3 . The device based on this new material in conjunction with a carbon counter electrode achieves a power conversion efficiency of 3.18% under the illumination of 100 mW cm −2, which is better than that of the reference compound (0.93%). These results indicate truxene core is a promising building block for hole-transporting material. Graphical abstract: Highlights: A novel truxene-based hole-transporting material was synthesized by a facile route. The truxene-based material exhibits high thermal stability and excellent solubility. This new material can be used for perovskite solar cells with carbon cathode.